Optimization of hot melt extrusion parameters for sphericity and hardness of polymeric face-cut pellets. (1st November 2016) - Alshetaili, Abdullah S.; Almutairy, Bjad K.; Alshahrani, Saad M.; Ashour, Eman A.; Tiwari, Roshan V.; Alshehri, Sultan M.; Feng, Xin; Alsulays, Bader B.; Majumdar, Soumyajit; Langley, Nigel; Kolter, Karl; Gryczke, Andreas; et al.
Abstract: The aim of this study was to formulate face-cut, melt-extruded pellets, and to optimize hot melt process parameters to obtain maximized sphericity and hardness by utilizing Soluplus ® as a polymeric carrier and carbamazepine (CBZ) as a model drug. Thermal gravimetric analysis (TGA) was used to detect thermal stability of CBZ. The Box–Behnken design for response surface methodology was developed using three factors, processing temperature ( °C), feeding rate (%), and screw speed (rpm), which resulted in 17 experimental runs. The influence of these factors on pellet sphericity and mechanical characteristics was assessed and evaluated for each experimental run. Pellets with optimal sphericity and mechanical properties were chosen for further characterization. This included differential scanning calorimetry, drug release, hardness friability index (HFI), flowability, bulk density, tapped density, Carr's index, and fourier transform infrared radiation (FTIR) spectroscopy. TGA data showed no drug degradation upon heating to 190 °C. Hot melt extrusion processing conditions were found to have a significant effect on the pellet shape and hardness profile. Pellets with maximum sphericity and hardness exhibited no crystalline peak after extrusion. The rate of drug release was affected mainly by pellet size, where smaller pellets released the drug faster. All optimized formulations were found to be of superior hardness and not friable. The flow properties of optimized pellets were excellent with high bulk and tapped density.